The effect of Dowex 50 x 4 on the stability of imidazolepyruvic acid - Thamavit, Chirasarit; Lim-Sylianco, Clara Y. (Quezon City Department of Chemistry, College of Arts and Sciences, University of the Philippines Diliman, 1967)
Imidazolepurivic acid is the alpha-keto analog of histidine. It has been obtained from the urinary metabolite of D-histidine from rats. It is the only compound known to be able to promote slow to moderate growth in the complete absence of histidine.
To study the effect of Dowex 50 x 4, a strong acidic cation exchanger, the urinary metabolite of D-histidine in rats was passed through a column of the former and eluted with ammonium hydroxide. The effluent was analysed quantitatively by paper chromatography and quantitatively by thin layer chromatography using Pauly reagent to detect the imidazoleacetic acid which was the expected decomposition product.
An increase in amount of imidazoleacetic acid after passing through the column is considered as a verification of the postulate that imidazolepyruvic acid is decomposed into imidazoleacetic acid.
The reaction mechanism proposed is a decarboxylation of the substrate followed by oxidation to form the imidazoleacetic acid.
Thesis (Bachelor of Science in Chemistry)--University of the Philippines Diliman, 1967.
Keywords: Imidazole; Pyruvic acid; Drug stability